More Favorable Short and Long-Term Outcomes for Screen-Detected Colorectal Cancer Patients - Spolverato, Gaya; Capelli, Giulia; Battagello, Jessica; Barina, Andrea; Nordio, Susi; Finotti, Elena; Mondi, Isabella; Da Lio, Corrado; Morpurgo, Emilio; Navarro, Josè Adolfo; Ceccato, Fabio; Perin, Alessandro; et al. (Frontiers in Oncology, 2021)
Background: Screening significantly reduces mortality from colorectal cancer (CRC). Screen detected (SD) tumors associate with better prognosis, even at later stage, compared to non-screen detected (NSD) tumors. We aimed to evaluate the association between diagnostic modality (SD vs. NSD) and short- and long-term outcomes of patients undergoing surgery for CRC. Materials and methods: This retrospective cohort study involved patients aged 50-69 years, residing in Veneto, Italy, who underwent curative-intent surgery for CRC between 2006 and 2018. The clinical multi-institutional dataset was linked with the screening dataset in order to define diagnostic modality (SD vs. NSD). Short- and long-term outcomes were compared between the two groups. Results: Of 1360 patients included, 464 were SD (34.1%) and 896 NSD (65.9%). Patients with a SD CRC were more likely to have less comorbidities (p= 0.013), lower ASA score (p= 0.001), tumors located in the proximal colon (p=0.0018), and earlier stage at diagnosis (p<0.0001). NSD patients were found to have more aggressive disease at diagnosis, higher complication rate and higher readmission rate due to surgical complications (all p<0.05). NSD patients had a significantly lower Disease Free Survival and Overall Survival (all p<0.0001), even after adjusting by demographic, clinic-pathological, tumor and treatment characteristics. Conclusions: SD tumors were associated with better long-term outcomes, even after multiple adjustment. Our results confirm the advantages for the target population to participate in the screening programs and comply with their therapeutic pathways.